Map lattices coupled by collisions - Keller, Gerhard; Liverani, Carlangelo (Communications in Mathematical Physics, 2009)
We introduce a new coupled map lattice model in which the weak interaction takes place via rare “collisions”. By “collision” we mean a strong (possibly discontinuous) change in the system. For such models we prove uniqueness of the SRB measure and exponential space-time decay of correlations.